1988
DOI: 10.1111/j.1600-0528.1988.tb00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal conditions in a randomly selected population in Switzerland

Abstract: The aim of the present study was to evaluate the periodontal conditions of a randomly selected population in the Canton of Berne, Switzerland. From a total of 350 selected persons, 206 (59%) attended the examinations. The Plaque Index (PlI), Gingival Index (GI) and Retention Index (RI), the width of the keratinized gingiva, pocket probing depth (PD) and loss of probing attachment (LA) were recorded on four surfaces per tooth in the entire dentition of the subjects. The statistical analyses were performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
5

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 9 publications
2
20
0
5
Order By: Relevance
“…The CPITN recordings have been applied in several studies worldwide [18][19][20][21] , since it has been recommended by the WHO to increase the international uniformity of epidemiological studies in periodontology. Standard recordings did not include direct measures of tissue destructions, which have been considered as limitation of the index [19,22] .…”
Section: Discussionmentioning
confidence: 99%
“…The CPITN recordings have been applied in several studies worldwide [18][19][20][21] , since it has been recommended by the WHO to increase the international uniformity of epidemiological studies in periodontology. Standard recordings did not include direct measures of tissue destructions, which have been considered as limitation of the index [19,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the distribution of periodontal disease by tooth type showed that molars were most often affected by gingivitis and periodontitis. On the other hand, the maxillary central incisors were the least periodontally involved tooth type 34 . Since CPI employs eight molars and two incisors, the overestimation of periodontal disease observed in the present study is understandable.…”
Section: Clinicalmentioning
confidence: 99%
“…Although buccal sites are more susceptible to loss of attachment due to non-bacterial processes, such as severe tooth brushing 33 , destructive periodontal disease is more frequent and severe in proximal sites compared to buccal and lingual periodontal sites 34 .…”
Section: Clinicalmentioning
confidence: 99%
“…The CPITN recordings have been applied in several studies worldwide (Pilot & Barmes 1987, Schürch et al 1988, Ö sterberg et al 1995, Bourgeois et al 1997) as it has been widely recommended (WHO 1997, Petersen & Ogawa 2005 to increase international uniformity. The CPITN is designed for rapid and practical assessment of various periodontal treatment needs in population surveys (Ainamo et al 1982).…”
Section: Discussionmentioning
confidence: 99%